The important role of cisplatin in the treatment of HPV-positive oropharyngeal cancer assessed by real-world data analysis. (October 2021) - Nauta, Irene H.; Klausch, Thomas; van de Ven, Peter M.; Hoebers, Frank J.P.; Licitra, Lisa; Poli, Tito; Scheckenbach, Kathrin; Brakenhoff, Ruud H.; Berkhof, Johannes; René Leemans, C.
Highlights: Causal inference allows robust statistics of non-randomized retrospective data. Causal inference adjusts for treatment assignment to simulate a randomized setting. Recent de-intensification trials proved the importance of cisplatin in HPV+ OPSCC. This study confirms the important therapeutic role of cisplatin in HPV+ OPSCC. Causal inference of real-world data complements evidence from RCTs. Abstract: Objectives: The prognostic advantage of human papillomavirus (HPV)-positive oropharyngeal squamous cell carcinoma (OPSCC) resulted in the initiation of treatment de-intensification studies. Two randomized controlled trials (RCTs) reported inferior survival of HPV-positive OPSCC treated with radiotherapy plus cetuximab compared to standard of care radiotherapy plus cisplatin. In this study we investigated whether the important role of cisplatin in the treatment of HPV-positive OPSCCs would also emerge from causal inference analyses of real-world data. Material and methods: A retrospective cohort of 263 advanced-stage OPSCC-patients from 5 European clinics was studied, treated with radiotherapy (RT) alone or cisplatin-based chemoradiotherapy (CRT) based on standard clinical indications. Causal inference was applied to adjust for treatment assignment, thereby simulating a randomized setting. Average treatment effect of concurrent cisplatin on overall survival (OS) probability was estimated using Bayesian Additive Regression Trees (BART) and Bayesian logistic regression. Results: Significantly better survival probabilities were found for HPV-positive OPSCC treated with CRT compared to RT alone (3-year OS probability 0.961 versus 0.798, p = 0.008). Conclusion: This study using causal inference of retrospective patient data confirms the important role of cisplatin in the treatment of HPV-positive OPSCC. Causal inference analyses of real-world data complements the evidence from the published RCTs.